Stress Hyperglycemia Ratio and Hemoglobin to RDW Ratio in Predicting the Outcomes of Thrombolysis-Treated Stroke: A Retrospective Cohort Study - Krongsut, Sarawut; Na-Ek, Nat (Archives of Academic Emergency Medicine, 2025)
Introduction: High stress hyperglycemia ratio (SHR) and low hemoglobin-to-red blood cell distribution width ratio (HB/RDW) are each known predictors of mortality in acute ischemic stroke (AIS). This study aimed to assess the predictive performance of high SHR (≥1.18) and low HB/RDW (≤0.76) together in stroke patients treated with thrombolysis. Methods: We retrospectively collected data from 345 AIS patients treated with thrombolysis. HB/RDW values were obtained from pre-recombinant tissue plasminogen activator complete blood counts; while fasting plasma glucose (FPG) and glycated hemoglobin (HbA1c) levels were measured in the morning after an 8–14-hour overnight fast. Patients were categorized into four groups based on SHR and HB/RDW levels. We used multivariable Poisson regression with robust variance to estimate risk ratios (RRs) and 95% confidence intervals (CIs). Models assessed associations with in-hospital mortality (IHM), early neurological deterioration (END), and functional outcomes at discharge and 3 months, adjusting for age, sex, prior stroke, pre-existing disability, myocardial infarction, atrial fibrillation, heart failure, chronic kidney disease, and malignancy. Propensity score weighting analysis was further conducted as a sensitivity analysis. Results: Among 345 patients, only 37 were in the high SHR (SHR+) and low HB/RDW (HB/RDW+) group. A total of 65 patients (18.8%) died during hospitalization. The SHR+ HB/RDW+ group had significantly higher risks of IHM (adjusted RR: 9.97, 95% CI: 4.95–20.08), END (adjusted RR: 2.95, 95% CI: 1.51–5.77), 3-month mortality (adjusted RR: 6.23, 95% CI: 3.49–11.12), and poor 3-month functional outcomes (adjusted RR: 2.86, 95% CI: 2.01–4.06) compared to the SHR- HB/RDW- group. These associations remained robust across sensitivity analyses. The combination of SHR ≥1.18 and HB/RDW ≤0.76 predicted IHM with an AuROC of 0.78 (95% CI: 0.73–0.83). Although the combined biomarker improved sensitivity and net benefit, its AUROC was not statistically superior to that of individual markers. Conclusions: Combined high SHR and low HB/RDW levels at admission significantly predict poor outcomes in thrombolysis-treated AIS, performing better than either biomarker alone. Further validation in larger, diverse cohorts is warranted.